Sistem Aplikasi Pengolahan Nilai Raport Pondok Pesantren 'Al Falah' Putri Kepel Ampel Wuluhan Jember: Application System for Report Card Processing at 'Al Falah' Islamic Boarding School for Girls, Kepel Ampel Wuluhan Jember - Indah Wahyuni (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
With advances in science and technology today, computers are now used in companies, agencies, and educational institutions. However, the problem experienced by the